Historien og fortællingen - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1982)
In his doctoral dissertation, “Den Kristne Grundfortælling” (The Fundamental Christian Story), Svend Bjerg pleads for the intimate connexion between Christianity and narrative. Christian belief is created by narrative, and the New Testament texts have to be understood as narrative, and treated as such. At the same time Historical Criticism of the Bible is rejected as a false way of treating Biblical narrative. In his article, the author proves that Svend Bjerg uses the category “story” with so wide a content that is loses its value as a concise category. Secondly, he shows that Svend Bjerg’s picture of Historical Criticism is not adequate. He critizises Svend Bjerg’s contraposition of story and history and he demonstrates how Svend Bjerg himself is unwilling to draw the consequences of his own view of Historical Criticism. The contraposition of story and history, therefore, is not helpful.